THE GENDERED IMPACT OF CORRUPTION: WOMEN AS VICTIMS OF SEXTORTION IN SOUTH AFRICA - Hagglund, Kirstin; Khan, Franaaz (Journal of Anti-Corruption Law, 2023)
Corruption affects people differently due to a range of factors, including gender, context, race, socio-economic status, power relations and vulnerability. Research suggests that corruption can affect women more adversely than it does men.1 This is because vulnerable groups are more susceptible to corruption, and women are often more vulnerable than men as they are viewed as easier targets. Furthermore, it follows that more vulnerable women are likely to be more adversely affected by corruption than those that are less vulnerable. The evidence generally shows that the gendered impact of corruption is related to societal gender roles, social inequality and discrimination. Thus, women's disadvantages in many areas of life result in greater vulnerability to corruption compared to men, who enjoy more power and protection, and better access to countervailing strategies. Corruption severely influences the extent to which women's rights are ensured and protected. In cases where women find themselves in a social, political, organisational or cultural context where they are more disempowered relative to men, and they are direct victims of corruption, their experiences of corruption can be more acute, and their avenues to respond to it more limited.2 In this article, the law pertaining to sextortion in South Africa is explored. The authors recommend that women must be brought into the public arena and information about public services be made widely available as this can be critical in reducing the differential impacts of corruption on them.